10.1159/000503210 (Inactive DOIs, 2000)
OBJECTIVES: Adverse childhood experiences (ACEs), i.e. child abuse or challenging circumstances in the family, are associated with various negative health outcomes in adulthood, such as cancer and heart disease, and there is some evidence for an association with oral health. We aimed to investigate whether there was an association between ACEs and adulthood caries experience, periodontal health, erosive tooth wear, and related behavior among the participants from the Northern Finland Birth Cohort 1986 (NFBC1986). METHODS: The study population consisted of 1690 cohort members who participated in a clinical dental examination at the age of 33-35 years. Calibrated dentists performed clinical examinations including caries experience (ICDAS converted to DMFS-score), periodontal status (pocket depth and bleeding on probing), and erosive tooth wear (BEWE-score). Family dysfunction data was collected objectively from cohort follow-up studies at ages 15-16 and 33-35, and national health care registers, and analyzed as Sample 1 (family dysfunction). Child abuse data was collected at ages 20-26 by a specific self-report questionnaire (Trauma And Distress Scale); data from 244 participants (of the 1690 cohort members) was available and constituted Sample 2 (child abuse). Bivariate and multivariate tests were conducted to examine the association between ACEs, caries experience, bleeding on probing, periodontal pocket depth, erosive tooth wear, smoking, toothbrushing and frequency of snacks. RESULTS: In Sample 1, participants with one or more family dysfunction factors had more caries experience (DMFS=19.4) than those with no family dysfunction (DMFS=16.6) and were more often smokers (26.1% vs 28.8%). In Sample 2, physical abuse was associated with increased bleeding on probing (43.9% vs 38.8%), smoking (26.0% vs 33.3%), insufficient toothbrushing (19.5% vs 33.3%) and increased frequency of snacks (14.3 vs 14.7). CONCLUSIONS: The results suggest that ACEs are associated with higher levels of dental caries, higher risk for periodontal disease and more harmful oral health behavior in adulthood.